Efeitos do exercício resistido de membros superiores na força e na funcionalidade do paciente com DPOC - Ike, Daniela (Universidade Federal de São Carlos, 2009)
The aim of this study was assess the effect of the resistance exercise in upper limb on the strength and functionality in COPD patients moderate to very severe. Methods: Twelve patients with clinical diagnosis of COPD were distributed into 2 groups: control (GC) and trained (GT). During 6 weeks, with frequency of 3 times a week, the GT carried out strength training with load of 80% of one repetition maximum (1RM) and GC performed bronchial hygiene sessions and functional respiratory reeducation. Before and after the treatment were carried out the 1RM test and the Pegboard and Ring Test (PBRT) in both groups. Results: After treatment observed significant increase of the strength muscular only in GT (increase of 52% in the supine and 22% in the pulley), and in the PBRT there were not significant difference in the number of moved rings in both groups. Conclusion: The upper limb strength training during 6 weeks was be able to improve the upper limb muscle strength, but not the functionality of COPD, assessed by PBRT, in patients with COPD moderate to very severe.
Keywords: Fisioterapia respiratória; Doença Pulmonar Obstrutiva Crônica (DPOC); Membros superiores; Reabilitação; Fisioterapia; Rehabilitation; Physiotherapy; Upper limb; Chronic obstructive pulmonary disease; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL